Pengaruh Kepemilikan Manajerial dan Kepemilikan Institusional pada Kebijakan Hutang Perusahaan : Sebuah Perspektif Theory Agency - Wahidahwati Wahidahwati (The Indonesian Journal of Accounting Research, 2013)
The purpose of this research is to test the effect of managerial ownership and institutional ownership to corporate policy in the perspective of agency theory. This research is based on the previous research by Moh’d, et al. (1998), which found that ownershipstructure influenced the debt ratio in order to minimize the agency conflict. The research is focused on manufacturing companies listed in Bursa Effek Jakarta for period 1995-1996. The method of data collection is done by using pooling method and give 61 firm year observation. The Statistical method used in this researchis multiple regression. The result of this research shows that managerial and institutional ownership have the negative and significant effect to the debt ratio. The result reflect that managerial and institutional ownership may replace in order to minimize the agency conflict.